Local Lagrange Interpolations Using Bivariate C2 Splines of Degree Seven on Triangulated Quadrangulations - Xuqiong Luo; Qikui Du (Journal of Mathematics)
A local Lagrange interpolation scheme using bivariate C2 splines of degree seven over a checkerboard triangulated quadrangulation is constructed. The method provides optimal order approximation of smooth functions.